Biomechanics of suplex in Greco-Roman wrestling: a qualitative and time-motion analysis of international competitions - Hoffmann, J.; Amici, C.; Minelli, C.; Borboni, A. (International Journal of Performance Analysis in Sport, 2023)
The suplex is one of the most important and spectacular offensive moves in Greco-Roman wrestling, and wrestling in general, but to date no published biomechanical study has systematically described it. We performed a qualitative biomechanical analysis to classify variants of suplex, and to split this complex move into phases and actions within them. As suplex efficacy highly depends on speed of execution, we analysed 80 suplex throws from publicly available videos of international matches at the highest level to describe the duration of the different phases and actions, and how these vary across variants of suplex. We observed a preference for belly-to-belly vs belly-to-back and for lateral vs frontal variants of suplex. We show differences in duration of important phases/actions across variants, including the preparation phase (longer for belly-to-back variants) and the back arch in the projection phase (longer for frontal variants), while we find no evidence of a difference in the frequency of win by fall. Our study provides a useful framework to evaluate and monitor suplex execution, through information to help choose a variant in specific match contexts, a systematic description of its complex motion to allow a more focused training, and "gold-standard" durations of its movement components.